Analysis Of The Success Of Digital-Based Agricultural Extension Programs In Rural Areas - Agmamsyahri (Agriculture Journal, 2025)
An inventive way to raise farmers' knowledge and proficiency in rural regions is through digital-based agricultural extension. The purpose of this study is to evaluate the extension program's effectiveness and how it affects farmers' satisfaction. 50 farmers participating in the initiative were given questionnaires and conducted in-depth interviews as part of the methodology. According to the findings, 75% of farmers learned new skills and 82% of farmers gained more information; on a Likert scale of 5, the average satisfaction level was 4.2. Technology adoption is nevertheless hampered by issues including low digital literacy and inadequate internet infrastructure, despite the program's effectiveness. According to the study's findings, enhancing digital literacy and building infrastructure are critical to the long-term viability of Indonesia's digitally based extension initiatives.